The early prehistory of Scotland - Pollard, Tony; Morrison, Alex (Dalrymple monograph ;, 1996)
"Bringing together the latest work on the Mesolithic in Scotland and Northern England, this book a much-needed reassessment of early prehistory from the key researchers in the area. Base firmly on archaeological evidence from recent excavations, this important book also includes work on the environmental background and on the history of the enquiry. Broad-based, comprehensive and thoroughly up-to-date, this will be an essential reference work for all those interested in early prehistoric Scotland."--Jacket